If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 0.2(x + -1) = 12 Reorder the terms: 0.2(-1 + x) = 12 (-1 * 0.2 + x * 0.2) = 12 (-0.2 + 0.2x) = 12 Solving -0.2 + 0.2x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2' to each side of the equation. -0.2 + 0.2 + 0.2x = 12 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + 0.2x = 12 + 0.2 0.2x = 12 + 0.2 Combine like terms: 12 + 0.2 = 12.2 0.2x = 12.2 Divide each side by '0.2'. x = 61 Simplifying x = 61

| [-9(-x)]-12=(4x)-8 | | x(x+5)=3450 | | -5y-10=20x | | 5p-7=-(7-5p) | | 2x+12=4x+22 | | -5-6=-7+x | | 8(1)-8=x | | 1.5y=-y+50 | | 11+4z+1z-6= | | x+1=-2+3 | | -5y+-10=20x | | -(n-1)=5-3n | | 2*3.14r=13 | | 6x=(x+5) | | x^6-2x^3=3 | | 14p-2+1p= | | 8(8)-8=x | | 5x-2y=8x-1 | | 6x+9x=32+13 | | 7x-11=80 | | 0.5(x-6.00)=-7.00 | | 6p-5=-9 | | 6p-5=-9 | | -74=9x-11 | | 19x-16=45-60 | | 5-5=13x+2x | | 14= | | 1b-3+6-2b= | | 9+6n=-93 | | 53x=26(2x+1) | | 26x^2-7=0 | | 3(b-8)+3=-23+3b | | 10x-(x+3)= | | 3(x+1)+5x=51 | | 2fgh-3g=10 | | 6(-3)-5+2(-3-2)=x | | 4x^2-36x+4y^2+28y-270=0 | | 4-8(-266t)= | | 9x+15-8x=-2-11 | | 4x=3y-1 | | 7x-7x=-10x-20+35-5x | | 9d+15-4d-8-5d= | | 6b+10=3b+9 | | 3(m+5)-6=3m+3 | | 3x+1=-9-5x | | 1.7b=39.1 | | 90p=100+70p | | 6Q-30-19=5 | | 12t+5t=6(t+2) | | 90x+30x=50+70x | | -12-x=-2(x+4) | | -3s+(-5s+1)= | | -3s+(-5s+1)= | | 128x^3-2x^5= | | .33(50+x)=80 | | 90+30x=50+70x | | -26d=-36a | | 2x-5-6-2x=11 | | n^2-11+10=0 | | -8-x=1 | | 6(1)-5+2(1-2)=x | | 6Q-11=5 | | 90+.30x=50+.70x | | 3x+16=-10-(2x-6) | | -4(5+8u)+2=38-4 |